“Não é certo a gente viver governado pelos outros quando a gente tem capacidade de fazer”: articulação e protagonismo Kaingang (Rio Grande do Sul, 1968-1985) - Flores, Andressa de Rodrigues (Universidade do Vale do Rio dos Sinos, 2023)
The present thesis has as its theme the Kaingang articulation, whose temporal and geographic cut contemplates the Kaingang people of some of the Indigenous Posts in the estate of Rio Grande do Sul, Brazil, namely Nonoai, Guarita, Cacique Doble, Votouro e Ligeiro, in a period that comprises the years 1968 to 1985, that is, from the extinction of the Indian Protection Service and the creation of the National Indian Foundation until the redemocratization period. The problem of the thesis is to identify and analyze the motivations, the characteristics and the effects of the articulation process of indigenous people in Rio Grande do Sul in the context of the military dictatorship. Based on the analysis of articles published in the press, especially in the newspapers Boletim Luta Indígena, Boletim do Cimi, O Estado de São Paulo, Folha de São Paulo, Correio do Povo, Zero Hora etc., from official sources produced by security and information forces in power during the time of military dictatorship and from sources produced by religious institutions, we seek to understand the process of articulation of the Kaingang indigenous people, linking it to the different ways of coping with situations of violence, vulnerabilities and conflicts that they experienced in the period encompassed by the thesis. To adress the different forms and evidence of indigenous protagonism, we use the theoretical contribution of New Indigenous History, especially in the reflections proposed by Santos and Felippe (2016, 2017, 2018). We also seek, resorting to Michel de Certeau (1998), to identify a nd discuss the governmental control strategies employed over the indigenous people and the tactics used by them to face them. We use the reflections of Haesbaert (2020), Quijano (2005, 2009) and Lugones (2014) to identify and discuss practices of violence against the Kaingang body and territory; from the productions of Tedesco et. al (2013, 2021) to address the issue of land disputes, and Brighenti (2012, 2013, 2020, 2021), Bicalho (2010a, 2010b), Baniwa (2007), Munduruku (2012) and Bittencourt (2000, 2007) to reconstitute and understand how the Kaingang articulation and the formation of the Indigenous Movement took place in Brazil. We are also interested in understanding the influence of religious organizations in this articulation process, since that, when investigating the effects and challenges to developmental policies that affected indigenous lands, we identified some characters involved in this process of formation of an indigenous movement in the south portion of the country, resulting from the articulation of the Kaingang, a theme still little explored by historiography in Rio Grande do Sul.
Keywords: Protagonismo Indígena; kaingang; FUNAI; Imprensa; Igreja; Ditadura Militar; Rio Grande do Sul; Indigenous protagonism; Press; Religion; Military Dictatorship; ACCNPQ::Ciências Humanas::História